PENGARUH MEDIA BAHAN ALAM TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK TELKOM PADANG - Dela Suryani; Rakimahwati; Yaswinda; Saridewi (STKIP Subang, 2026)
This study aims to determine the effect of natural material media on the counting ability of children aged 5-6 years at Kindergarten Telkom Padang. This research used a quantitative approach with a quasi-experimental design. The sample consisted of 30 children divided into an experimental group (class B2, 15 children) taught using natural material media and a control group (class B4, 15 children) taught using conventional number-card media. Data were collected through observation using a performance test instrument covering five indicators of early counting ability and analyzed using an independent sample t-test after normality and homogeneity assumptions were met. It can be concluded that natural material media has a significant effect on the counting ability of children aged 5-6 years, providing them with a concrete, engaging, and meaningful learning experience that teachers can adopt as an alternative to conventional media.